The student's guide to writing. spelling, punctuation and grammar - Peck, John.; Coyle, Martin (England : New York : Palgrave macmillan, 2005)
The new edition of this best-seller guides students through the process of improving their writing, showing them how to construct a sentence, a paragraph and an essay. The authors have revised the original edition to make their explanations even clearer, included a "Spot the Mistake" section, and added an index for easier navigation.
Includes index.
Keywords: English language -- Grammar; English language -- Orthography and spelling; English language -- Punctuation